A zinc finger protein shapes the temperature adaptability of a cosmopolitan pest - Xin Miao; Fang Cao; Xiao-Fei Yu; Tian-Pu Li; Hai-Yin Su; Jiao Guo; Gui-Lei Hu; Bing-Wei Chen; Min-Sheng You; Yuan-Yuan Liu; Gao-Ke Lei; Shijun You (Open Biology)
Global climate change is characterized by increased extreme temperatures affecting insects at all trophic levels. Zinc finger proteins (ZFPs) are key regulators of gene expression and cell differentiation in eukaryotes, essential for stress resistance in both animals and plants. Using CRISPR/Cas9 for gene deletion, this study predicted and examined the structure of ZFP320 in the diamondback moth (Plutella xylostella) and investigated its function in temperature stress response through a comprehensive age-stage, two-sex life table analysis. We found ZFP320 encodes a 387 amino acid protein (43 kDa) with no transmembrane domains, featuring a ZnF-C2H2 domain. Quantitative fluorescence analysis showed that ZFP320 expression increased under high temperatures. ZFP320 knockout altered antioxidant gene expression, resulting in higher levels of superoxide dismutase and catalase in mutant strains compared with wild-type strain. Life table analysis revealed that the mutant strains had shorter fecundity and oviposition periods under both normal and high temperatures. Additionally, mutant strains exhibited lower parameters (r, λ, R0), as well as reduced survival rates and critical thermal maxima. Notably, PxZFP320 plays a crucial role in temperature adaptation, paving the way for future investigations on the significance of ZFPs in P. xylostella’s temperature tolerance.